2019
DOI: 10.5194/se-10-621-2019
|View full text |Cite
|
Sign up to set email alerts
|

Experimental grain growth of quartz aggregates under wet conditions and its application to deformation in nature

Abstract: Abstract. Grain growth of quartz was investigated using two quartz samples (powder and novaculite) with water under pressure and temperature conditions of 1.0–2.5 GPa and 800–1100 ∘C. The compacted powder preserved a substantial porosity, which caused a slower grain growth than in the novaculite. We assumed a grain growth law of dn-d0n=k0fH2Orexp⁡(-Q/RT)t with grain size d (µm) at time t (seconds), initial grain size d0 (µm), growth exponent n, a constant k0 (µmn MPa−r s−1), water fugacity fH2O (MPa) with the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
49
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(52 citation statements)
references
References 68 publications
2
49
1
Order By: Relevance
“…Using temperatures of 650°C–750°C and pressures of 0.7–0.75 GPa for steady‐state deformation in the Nusfjord mylonitized pseudotachylytes (Menegon et al, ), and water fugacities calculated for these conditions (Tödheide, ), the minimum period necessary for transformation from the fine‐grained recrystallized quartz to the foam texture ranges from 1–100 years, inversely proportional to temperature (Figure c). The grain growth parameters of Wightman et al, are somewhat pressure dependent, but those of Fukuda et al () are not, excepting the input of water fugacity. Although the more recent work of Fukuda et al suggested that the temperature dependence of the Wightman et al () grain growth parameters might be overestimated, the timescales estimated by both methods are very similar under the Nusfjord deformation conditions.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Using temperatures of 650°C–750°C and pressures of 0.7–0.75 GPa for steady‐state deformation in the Nusfjord mylonitized pseudotachylytes (Menegon et al, ), and water fugacities calculated for these conditions (Tödheide, ), the minimum period necessary for transformation from the fine‐grained recrystallized quartz to the foam texture ranges from 1–100 years, inversely proportional to temperature (Figure c). The grain growth parameters of Wightman et al, are somewhat pressure dependent, but those of Fukuda et al () are not, excepting the input of water fugacity. Although the more recent work of Fukuda et al suggested that the temperature dependence of the Wightman et al () grain growth parameters might be overestimated, the timescales estimated by both methods are very similar under the Nusfjord deformation conditions.…”
Section: Discussionmentioning
confidence: 93%
“…Also shown is the dry dislocation creep flow law for an anorthite‐diopside aggregate (grey curve; Dimanov & Dresen, ) to represent the hypothetical viscous deformation of the bulk anorthosite. The inset magnifies the mixed flow laws at low flow stress; (b) microstructures observed in quartz in mylonitized pseudotachylytes in Nusfjord related to relaxation of stress and strain rates over time after some perturbation, for example, seismic slip; and (c) static grain growth of quartz from an initial grain size of 6.5 μm modeled for Nusfjord deformation temperatures and pressures using the quartz grain growth parameters of Wightman et al () and Fukuda et al ().…”
Section: Discussionmentioning
confidence: 99%
“…8). However, unlike polygonal structures that result from static grain growth (e.g., Fukuda et al 2019), the actual grain shapes in dynamically recrystallized quartz rocks of the type-I and type-III are not close to cubes or tetradecahedra, and grain boundaries show curved or serrated morphologies (Takahashi et al 1998). Moreover, grain size distribution in dynamic recrystallization is close to lognormal, which means that the grains smaller than the average size are large in number (Shimizu 1998(Shimizu , 1999.…”
Section: Discussionmentioning
confidence: 99%
“…addition, the high activation enthalpy determined byWightman et al (2006) leads to slower growth rates when extrapolated to crustal temperatures. As for the grain growth law determined byFukuda et al (2019), the uncertainty in Qg is relatively large. This uncertainty partly reflects that most of their 1000°C grain growth experiments show slower grain growth than 900°C experiments (seeFigure 10in Fukuda et al, 2019).…”
mentioning
confidence: 99%
“… is empirically fit in each plot. Fukuda19 and Wightman06 refers to the grain growth laws developed byFukuda et al (2019) andWightman et al (2006), respectively.…”
mentioning
confidence: 99%